Zakat dan Upaya Mengentaskan Kemiskinan - Nurwati Nurwati; Heni Hendrawati (Universitas Muhammadiyah Magelang, 2019)
The purpose of this study is to analyze the impact of zakat utilization on the effort of poverty alleviation. This study was conducted through a literature study approach. The results indicate that the utilization of zakat is increasingly visible in its contribution to support the government's efforts to poverty alleviation. The zakat was focused on the poor and allocated to the social humanitarian and education sectors. The implication of this finding is that the optimization of the potential of zakat will be able to bring economic prosperity to the people which is certainly encouraged by the participation of all elements of the nation